2022
DOI: 10.1083/jcb.202111077
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal endolysosomal transport and lysosomal functionality in maintaining axonostasis

Abstract: Lysosomes serve as degradation hubs for the turnover of endocytic and autophagic cargos, which is essential for neuron function and survival. Deficits in lysosome function result in progressive neurodegeneration in most lysosomal storage disorders and contribute to the pathogenesis of aging-related neurodegenerative diseases. Given their size and highly polarized morphology, neurons face exceptional challenges in maintaining cellular homeostasis in regions far removed from the cell body where mature lysosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 166 publications
(289 reference statements)
1
39
0
Order By: Relevance
“…Spatacsin is present at these sites and its regulation of lysosomal repartition along the axon is concordant with this finding. Moreover, several recent papers have highlighted the importance of axonal lysosomal trafficking in the development of neurodegenerative disease (Lie and Nixon, 2019; Roney et al, 2022). In SPG11 models, previous work has shown that cultured neurons deprived of spatacsin presented axonal instability (Pérez-Brangulí et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatacsin is present at these sites and its regulation of lysosomal repartition along the axon is concordant with this finding. Moreover, several recent papers have highlighted the importance of axonal lysosomal trafficking in the development of neurodegenerative disease (Lie and Nixon, 2019; Roney et al, 2022). In SPG11 models, previous work has shown that cultured neurons deprived of spatacsin presented axonal instability (Pérez-Brangulí et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The coordination of this bidirectional transport is particularly important for polarized cells such as neurons. However, the mechanisms regulating the coordination of anterograde or retrograde transports of lysosomes are not clearly established (Roney et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Axons are insulated from extracellular fluid by several layers of myelin sheets formed by oligodendroglia that limit their access to extracellular glucose and lactate. Therefore, lactate is supplied by surrounding oligodendroglial processes through their MCT1 to peri-axonal space, from where it is taken up by axonal MCT2 and used for acetyl-CoA and ATP synthesis in axonal mitochondria [ 69 , 70 ]. Fractions of lactate and glucose are also provided by astrocytes that contact axons at nodes of Ranvier’s.…”
Section: Origin and Metabolic Role Of Axonal Acetyl-coamentioning
confidence: 99%
“…In innervated niches, autophagic stress caused by dysfunction of autophagosome-lysosome fusion is lethal to highly differentiated neurons ( Farfel-Becker et al, 2020 ). It is an indisputable fact that deficits in neuronal lysosome function and dysfunction of autophagy result in neurodegeneration ( Roney et al, 2022 ). Based on this, we hypothesize that blockage of the autophagy flux by chloroquine and hydroxychloroquine not only diminishes the positive effect in maintaining the innervated niche homeostasis but even leads to lethal autophagic stress.…”
Section: Drug Repurposing For Cancer Therapy: Targeting Autophagy In ...mentioning
confidence: 99%